Gogol’s Vij and L.N. Tolstoy’s War and Peace in V.V. Mayakovsky’s Poem War and Peace - Shul’ts, Sergei (Slavica, 2021)
Representing himself in his poem War and Peace in the form of a fictional "absolute unit" - the new Vij - Mayakovsky demonstrates the infernality of a new type, in comparison with Gogol’s one. Mayakovsky’s ideacontrasts with Tolstoy’s pacifism and the idea of "eternal peace" (the novel War and Peace). Unlike Tolstoy, refusing to notice and recognize the real diversity in the manifestations of man and the human principle, Mayakovsky reduces all people, their thoughts and concerns to their personal ideas.